(untitled) (UNIZIK Journal of STM Education, 2024)
Study habits play a very important role in academic life of students. Academic success or failures of students depend on their study habits. This study examines the influence of good study habits on the academic performance of students in mathematics in senior secondary schools in Ogun state, Nigeria.